Interrelation of competitive activity indicators, special, physical and functional fitness of highly qualified bmx cyclists - G.N. Semaeva; P.V. Kvashuk; P.P. Kostyukov; M.S. Chernyshov (Theory and Practice of Physical Culture, 2023)
Objective of the study was to reveal the relationship between the indicators of competitive activity, special physical and functional readiness of highly qualified BMX cyclists. Methods and structure of the study. 10 BMX female cyclists of the qualification Master of Sports and Master of Sports of international class took part in the scientific work. The competitive activity of BMX cyclists was studied at two stages of the BMX Cycling World Cup (Zolder, Belgium). The following performance indicators of competitive activity were recorded: the best time and rating of athletes during the passage of the starting acceleration section (distance section - start and starting acceleration on the ramp) among all participants in the competition; the best time and rating of athletes among all participants in the competition; final place in the protocol of the competition. The functional state of the CNS and the rate of formation of sensorimotor reactions were determined on the basis of a simple and complex visual-motor reaction using the device "Psychophysiologist - UPFT 1/30" (Russia), indicators of reaction time and reaction time standard deviation were recorded. Results and conclusions. It is shown that the effectiveness of the start, the rating of the participants in the competitions in terms of the best time and place to overcome the distance correlates with the volume of the muscle mass of the body of the cyclists, the functionality of the central nervous system, the speed and stability of the formation of sensorimotor reactions.